Gender-based eating norms, the family environment and food intake among Costa Rican adolescents - Monge Rojas, Rafael (2021)
Objective: To examine the association between family environment variables (parenting styles, family meal atmosphere), gender-based stereotypes, and food intake in Latin American adolescents. Design: Structural equation modeling applied to cross-sectional data, 2017. Setting: Urban and rural sites of San José, Costa Rica. Participants: n = 813; 13-18 years old. Results: Data suggest direct associations between gender-based stereotypes and intake of fruits and vegetables (FV) (β = 0.20, p < 0.05), unhealthy foods (fast food, FF) (β = -0.24, p < 0.01), and ultra-processed foods (UPF) (β = -0.15, p < 0.05) among urban girls; intake of legumes among rural girls (β = 0.16, p < 0.05) and intake of sugar-sweetened beverages (SSB) among rural boys (β = 0.22, p < 0.05). Family meal atmosphere was associated with legume intake (β = 0.19, p < .05) among rural girls. Authoritative parenting style was associated with FV intake (β = 0.23, p < 0.05) among urban boys and FF intake (β = 0.17, p < 0.05) among urban girls. Authoritarian parenting style was associated with FV consumption (β = 0.19, p < 0.05) among rural boys, and with SSB and FF consumption (β = 0.21, p < 0 .05; β = 0.14, p < 0.05, respectively) among urban girls. Conclusions: Findings are the first to describe the complex family environment and gender-based stereotypes within the context of a Latin American country. They emphasize the need for culturally relevant measurements to characterize the sociocultural context in which parent-adolescent dyads socialize and influence food consumption.